2019
DOI: 10.1051/mbcb/2019011
|View full text |Cite
|
Sign up to set email alerts
|

Krokodil (Desomorphine)-induced osteonecrosis of the maxilla: a case report and literature review

Abstract: Introduction: Desomorphine is an opioid formerly used to treat acute pain. It is simple to manufacture, which has recently led to an increase in its clandestine production under the name “Krokodil”. This article presents a case of oral problems related to its use first ever reported in France. Observation: A 36-year-old male patient presented with bone exposure in sector 1. He admitted to actively consuming “Krokodil IV” for several years. In the course of the clinical and radiological examinations, the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…178 Subsequently, cases (both confirmed and suspected) have been reported in other European countries, such as France, 204 Italy, 205 Norway, 206 Spain, 207 and Poland, 208,209 with a significant part of them imported from Eastern Europe through immigrants from former Soviet republics. 204 It is noteworthy that various reviews mention cases reported in the Czech Republic, Sweden, Belgium, and Portugal, 190,208,210,211 but reliable information about these cases could not be found by the authors of the current review. In North America, some cases have been reported in both Canada 212,213 and the US 186,191,214−218 (in newspapers and scientific articles), most of which are heavily based on patient history and the admission of krokodil use by drug users.…”
Section: Desomorphine (Krokodil)mentioning
confidence: 71%
See 3 more Smart Citations
“…178 Subsequently, cases (both confirmed and suspected) have been reported in other European countries, such as France, 204 Italy, 205 Norway, 206 Spain, 207 and Poland, 208,209 with a significant part of them imported from Eastern Europe through immigrants from former Soviet republics. 204 It is noteworthy that various reviews mention cases reported in the Czech Republic, Sweden, Belgium, and Portugal, 190,208,210,211 but reliable information about these cases could not be found by the authors of the current review. In North America, some cases have been reported in both Canada 212,213 and the US 186,191,214−218 (in newspapers and scientific articles), most of which are heavily based on patient history and the admission of krokodil use by drug users.…”
Section: Desomorphine (Krokodil)mentioning
confidence: 71%
“…Since its appearance in Russia, the drug quickly spread to other neighboring former Soviet republics, especially Ukraine (which had around 20 000 cases in 2011), , as well as Georgia, Armenia, , and Kazakhstan. , The first western European country to report cases of krokodil use was Germany in 2011 . Subsequently, cases (both confirmed and suspected) have been reported in other European countries, such as France, Italy, Norway, Spain, and Poland, , with a significant part of them imported from Eastern Europe through immigrants from former Soviet republics . It is noteworthy that various reviews mention cases reported in the Czech Republic, Sweden, Belgium, and Portugal, ,,, but reliable information about these cases could not be found by the authors of the current review.…”
Section: Desomorphine (Krokodil)mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the toxic substances in the manufacturing process of this highly addictive drug, as well as the injectable equipment and hygiene, the risk of infection is much larger and more severe than that of any other drug with the same administration [64]. Some of these drugs have also shown to cause necrosis of the mandible and maxilla [65,66].…”
Section: Opioidsmentioning
confidence: 99%